Detection of the 5p – 4f orbital crossing and its optical clock transition in Pr9+ - H. Bekker (Nature Portfolio, 2019)
Atomic clocks are based on the frequency of optical transitions and offer high precision. Here the authors demonstrate a configuration crossing in the highly charged ion praseodymium (Pr$${}^{9+}$$ 9+ ) and determine the frequency of a potential reference transition for a highly charged ion clock.